A África em nós: saberes ubuntu na formação inicial docente no curso de Pedagogia (UFMA/ Campus Codó) - SOUSA, Soraia Lima Ribeiro de (2022)
In Brazil, over the years and from the struggle of the black movement, the reality of the black population has been discussed and all the implications of recognizing black in this country, whose territory has racism, as an organizing element of the social structure. The ideologies of racism educate, guide and regulate the place and non-place of the black person in Brazilian society, organizing social relations and establishing what should be considered beautiful, what may or may not be accepted in everyday practices. Even recognizing that we have made some progress, through social struggles, there is still much to be studied and deepened in relation to the participation of black people in this reality, if we want to build a fair and democratic society. This research seeks to (re)think Brazilian education, especially initial teacher training, from an Afrocentric perspective, aiming to investigate places of appropriation of UBUNTU knowledge in initial teacher training in the Pedagogy Course at UFMA/ Campus Codó - MA, considering the Education of Ethnic-Racial Relations – ERER. About the theoretical and methodological perspective, it is a participatory research with a qualitative nature, which adopting the assumptions of decolonial and Afrocentric epistemic and theoretical perspectives. It carries out a bibliographic and documentary survey, and together with the everyday study, adopts the conceptual bases of sociopoetics regarding the realization of Afrocentric workshops, aiming at the production of narratives in relation to student knowledge about UBUNTU. In order to reflect on ubuntu based on ethnic-racial relations in initial teacher training, we bring the dialogue with authors such as Asante (2009), Castiano (2010; 2013), Certeau (1998), Dussel (2016), Freire (1987). ; 1996), Kilomba (2019), Machado (2018), Mignolo (2017), Nascimento (2016), Nogueira (2011; 2014), Oliveira (2008), Ramose (1999; 2010); Silva (2004; 2013), among others, with the aim of dialoguing about concepts such as: Decoloniality and Afrocentricity; UBUNTU knowledge; Education of Ethnic- Racial Relations and Initial Teacher Training in Brazil. From the beginning of the Amen-em-ope barge, as a metaphor, we made our journey back to Africa in search of references to discuss Brazilian education, especially initial teacher training. The research results show that it is possible to recognize ubuntu knowledge and Africanities in the ethnic-racial relations built in the Pedagogy course at UFMA/Codó, in the PPC of the course, and in the daily routine of initial teacher training. Such relationships permeated by the confections of love, interdependence, recognition, matrilineage, common objective, belonging and others, have built what we are calling UBUNTUISM pedagogy, whose formative practices are based on Afrocentric values, enabling the exercise of Afro-teaching by teachers. You are in training.